Syntheses and characterization of mono and dinuclear complexes of platinum group metals bearing benzene-linked bis(pyrazolyl)methane ligands - Prasad, Kota Thirumala; Therrien, Bruno; Rao, Kollipara Mohan (My University, 2010)
Reaction of the benzene-linked bis(pyrazolyl)methane ligands, 1,4-bis{bis(pyrazolyl)-methyl}benzene (L1) and 1,4-bis{bis(3-methylpyrazolyl)methyl}benzene (L2), with pentamethylcyclopentadienyl rhodium and iridium complexes [(η5-C5Me5)M(μ-Cl)Cl]2 (M = Rh and Ir) in the presence of NH4PF6 results under stoichiometric control in both, mono and dinuclear complexes, [(η5-C5Me5)RhCl(L)]+ {L = L1 (1); L2 (2)}, [(η5-C5Me5)IrCl(L)]+ {L = L1 (3); L2 (4)} and [{(η5-C5Me5)RhCl}2(μ-L)]2+ {L = L1 (5); L2 (6)}, [{(η5-C5Me5)IrCl}2(μ-L)]2+ {L = L1 (7); L2 (8)}. In contrast, reaction of arene ruthenium complexes [(η6arene)Ru(μ-Cl)Cl]2 (arene = C6H6, p-iPrC6H4Me and C6Me6) with the same ligands (L1 or L2) gives only the dinuclear complexes [{(η6-C6H6)RuCl}2(μ-L)]2+ {L = L1 (9); L2 (10)}, [{(η6-p-iPrC6H4Me)RuCl}2 (μ-L)]2+ {L = L1 (11); L2 (12)} and [{(η6-C6Me6)RuCl}2(μ-L)]2+ {L = L1 (13); L2 (14)}. All complexes were isolated as their hexafluorophosphate salts. The single-crystal X-ray crystal structure analyses of [7](PF6)2, [9](PF6)2 and [11](PF6)2 reveal a typical piano-stool geometry around the metal centers with six-membered metallo-cycle in which the 1,4-bis{bis(pyrazolyl)-methyl}benzene acts as a bis-bidentate chelating ligand.
Keywords: Arene-ligands; Bis(pyrazolyl)methane; Ruthenium; Rhodium; Iridium